O&G, Geothermal Systems, and Natural Hydrogen Well Drilling: Market Analysis and Review - Nascimento, Andreas [UNESP]; Mantegazini, Diunay Zuliani [UNESP]; Mathias, Mauro Hugo [UNESP]; Reich, Matthias; Hunt, Julian David (MDPI, 2025)
Developing clean and renewable energy instead of the ones related to hydrocarbon resources has been known as one of the different ways to guarantee reduced greenhouse gas emissions. Geothermal systems and native hydrogen exploration could represent an opportunity to diversify the global energy matrix and lower carbon-related emissions. All of these natural energy sources require a well to be drilled for its access and/or extractions, similar to the petroleum industry. The main focuses of this technical–scientific contribution and research are (i) to evaluate the global energy matrix; (ii) to show the context over the years and future perspectives on geothermal systems and natural hydrogen exploration; and (iii) to present and analyze the importance of developing technologies on drilling process optimization aiming at accessing these natural energy resources. In 2022, the global energy matrix was composed mainly of nonrenewable sources such as oil, natural gas, and coal, where the combustion of fossil fuels produced approximately 37.15 billion tons of CO2 in the same year. In 2023, USD 1740 billion was invested globally in renewable energy to reduce CO2 emissions and combat greenhouse gas emissions. In this context, currently, about 353 geothermal power units are in operation worldwide with a capacity of 16,335 MW. In addition, globally, there are 35 geothermal power units under pre-construction (project phase), 93 already being constructed, and recently, 45 announced. Concerning hydrogen, the industry announced 680 large-scale project proposals, valued at USD 240 billion in direct investment by 2030. In Brazil, the energy company Petroleo Brasileiro SA (Petrobras, Rio de Janeiro, Brazil) will invest in the coming years nearly USD 4 million in research involving natural hydrogen generation, and since the exploration and access to natural energy resources (oil and gas, natural hydrogen, and geothermal systems, among others) are achieved through the drilling of wells, this document presents a technical–scientific contextualization of social interest.
Keywords: drilling; energy conversion; geothermal; hydrogen; petroleum; renewable energy